Systems view of Bacillus subtilis pellicle development - Mojca Krajnc; Polonca Stefanic; Rok Kostanjšek; Ines Mandic-Mulec; Iztok Dogsa; David Stopar (npj Biofilms and Microbiomes, 2022)
Abstract In this study, we link pellicle development at the water–air interface with the vertical distribution and viability of the individual B. subtilis PS-216 cells throughout the water column. Real-time interfacial rheology and time-lapse confocal laser scanning microscopy were combined to correlate mechanical properties with morphological changes (aggregation status, filament formation, pellicle thickness, spore formation) of the growing pellicle. Six key events were identified in B. subtilis pellicle formation that are accompanied by a major change in viscoelastic and morphology behaviour of the pellicle. The results imply that pellicle development is a multifaceted response to a changing environment induced by bacterial growth that causes population redistribution within the model system, reduction of the viable habitat to the water–air interface, cell development, and morphogenesis. The outcome is a build-up of mechanical stress supporting structure that eventually, due to nutrient deprivation, reaches the finite thickness. After prolonged incubation, the formed pellicle collapses, which correlates with the spore releasing process. The pellicle loses the ability to support mechanical stress, which marks the end of the pellicle life cycle and entry of the system into the dormant state.